Will REDD+ Safeguards Mitigate Corruption? Qualitative Evidence from Southeast Asia. Issue 10 (3rd October 2019) - Williams, David Aled; Dupuy, Kendra E.
Abstract: High levels of faith and finance are being invested in REDD+ as a promising global climate change mitigation policy. Since its inception in 2007, corruption has been viewed as a potential impediment to the achievement of REDD+ goals, partly motivating 'safeguards' rolled out as part of national REDD+ readiness activities. We compare corruption mitigation measures adopted as part of REDD+ safeguards, drawing on qualitative case evidence from three Southeast Asian countries that have recently piloted the scheme: Indonesia, the Philippines, and Vietnam. We find that while REDD+ safeguards adopt a conventional principal-agent approach to tackling corruption in the schemes, our case evidence confirms our theoretical expectation that REDD+ corruption risks are perceived to arise not only from principal-agent type problems: they are also linked to embedded pro-corruption social norms. This implies that REDD+ safeguards are likely to be at best partially effective against corruption, and at worst will not mitigate corruption at all.